Systèmes Agroforestiers A Garcinia Kola Heckel Au Sud-Est Du Bénin : Distribution Géographique, Connaissances Endogènes Et Retombées Financières - Codjia, Sylvie; Aoudji, Augustin; Koura, Kourouma; Ganglo, Jean Cossi (European Scientific Journal, ESJ, 2018)
This study was carried out in three districts (Avrankou, Adjarra, and Ifangni) of south-eastern Benin, and aimed to analyze the socio-economic and ethnobotanical importance of Garcinia kola Heckel, in order to contribute to their sustainable management. Focus groups were conducted with three groups, composed of 10 owners of G. kola per district each and the result showed that Garcinia kola Heckel became extinct in their naturally occurring state in Benin. Besides, a survey was conducted among 140 owners of G. kola randomly selected in the study area. The results showed that the average number of G. kola feet per owner varies between 3 and 4, and the annual income generated from seeds marketing by an owner is XOF 1036000 in Adjarra district, XOF 356250 in Avrankou district, and XOF 290892 in Ifangni district. Furthermore, the ethnobotanical study showed that G. kola organs are well known and used by local people for medicine, food (for both humans and animals), commercial, spiritual purpose, and for timber and shading. The medicinal use was the most widespread with a diversity of uses (UD = 0.64 in Adjarra, UD = 0.61 in Avrankou and UD = 0.68 in Ifangni). The old men held more knowledge about the use of various organs of the species (ID = 0.91, IE = 0.91), while young women hold less knowledge (ID = 0.20, IE = 0.20). The seeds are the most common part used regardless of the district considered.